1994
DOI: 10.1002/1097-0142(19940301)73:5<1383::aid-cncr2820730512>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial adenocarcinoma with endometrioid features and prominent neuroendocrine differentiation. A variant of fetal adenocarcinoma

Abstract: An endobronchial tumor, resected from a 77‐year‐old man, had an endometrioid histologic pattern consistent with fetal adenocarcinoma. A distinctive feature of the neoplasm was prominent neuroendocrine differentiation, including single, discrete neuroendocrine cells; aggregates of neuroendocrine cells resembling miniature carcinoid tumors; and a single focus of undifferentiated small cell carcinoma. Immunohistochemical staining of neuroendocrine cells revealed the presence of neuronspecific enolase, chromograni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…[3] Histologically the tumor is composed of neoplastic glands and tubules lined by non-ciliated columnar cells, with infra-and supranuclear vacuoles mimicking secretory endometrial glands. [6] These glands are rich in glycogen, as demonstrated by the PAS staining.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[3] Histologically the tumor is composed of neoplastic glands and tubules lined by non-ciliated columnar cells, with infra-and supranuclear vacuoles mimicking secretory endometrial glands. [6] These glands are rich in glycogen, as demonstrated by the PAS staining.…”
Section: Discussionmentioning
confidence: 91%
“…[3] Well-differentiated fetal adenocarcinoma is of low-grade malignant potential and associated with a low mortality rate, hence, it is important to identify this tumor, based on the age, gender of the patients, cytological and nuclear features of the glands, and appearance of the stroma. [6,10] Poor prognosis is associated with the presence of thoracic lymphadenopathy, initial metastases, and tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…M orules have been reported in well differentiated fetal adenocarcinoma of the lung (WDFA) and in pulmonary blastoma (PB), [1][2][3][4][5][6] and it has also been reported that morules show neuroendocrine differentiation. Morule formation in such tumours has also been reported to be associated with b catenin gene mutation.…”
mentioning
confidence: 99%
“…The presence of characteristic extranuclear vacuoles, rich in glycogen, makes adenocarcinoma resemble uteral mucosa in the secretion phase [4]. The specific feature of this carcinoma is the presence of argyrophil cells with neurosecretion activity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the patients with a diagnose of a poorly differentiated form of this tumour, with a high-grade of malignancy, the prognosis depends also on morphological components of the adenocarcinoma which are present in the architecture of fetal adenocarcinoma [5].…”
Section: Introductionmentioning
confidence: 99%